Sepsis pada Pneumonia: Literature Review - Farhana, Shabrina; Wahyuni, Ari; Lisiswanti, Rika (Medula, 2024)
Sepsis is a clinical syndrome that occurs as a complication of severe infection and systemic inflammation and widespread tissue damage. Over the past three decades, the incidence of sepsis has continued to increase and has become the leading cause of death compared to other common diseases in Western countries. The incidence of sepsis reaches 750,000 every year with mortality reaching 50% in patients experiencing sepsis and septic shock. Pneumonia is the most common primary infection that occurs in sepsis patients. Pneumonia ranks third highest worldwide. Pneumonia sufferers with sepsis account for 40% of all pneumonia sufferers. Severe sepsis can be triggered by infections that occur during medical treatment or can also occur from community-acquired infections (Community Acquired Pneumonia). The aim of this literature review is to provide an overview of epidemiology, pathophysiology, clinical manifestations, and therapy that can be carried out in patients with pneumonia complicated by sepsis. The results of this literature study show that clinical manifestations in patients are influenced by the location of the infection, the type of organism, and the severity or lightness of the infection. Therapy that can be carried out in patients with pneumonia with sepsis is initial resuscitation which includes administering 0.9% NaCL for 6 hours and vasopressors to maintain the patient's hemodynamics, as well as administering empiric antibiotics followed by antibiotics according to the culture results and resistance in the patient.